Political salience and regime resilience - Steffen Huck; Macartan Humphreys; Sebastian Schweighofer-Kodritsch (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2023)
We study a version of a canonical model of attacks against political regimes where agents have an expressive utility for taking political stances that is scaled by the salience of political decision-making. Increases in political salience can have divergent effects on regime stability depending on costs of being on the losing side. When regimes have weak sanctioning mechanisms, middling levels of salience can pose the greatest threat, as regime supporters are insufficiently motivated to act on their preferences and regime opponents are sufficiently motivated to stop conforming. Our results speak to the phenomenon of charged debates about democracy by identifying conditions under which heightened interest in political decision-making can pose a threat to democracy in and of itself.
Keywords: C72; D74; 330; Democracy; salience; insurgence